Comparison of mastery criteria applied to individual targets and stimulus sets on acquisition of tacts, intraverbals, and listener responses. Issue 4 (10th July 2022) - Cordeiro, Maria Clara; Kodak, Tiffany; Reidy, Jessi; Stoppleworth, Abigail; Zelinski, Karly; Jainga, Andrea
Abstract : Mastery criteria can be applied to individual targets or stimuli organized into sets. Wong et al. (2021) and Wong and Fienup (2022) found that participants who received special education services learned sight words more rapidly when an individual target mastery criterion was applied. The current study replicated and extended these findings across novel skills. Five participants with ASD received tact or intraverbal training in Experiment 1, and 2 participants with ASD received auditory–visual conditional discrimination training (AVCD) in Experiment 2. In both experiments, mastery criteria were applied to targets and stimulus sets to compare sessions to mastery. Results showed the target mastery criterion required fewer sessions of tact training for 3 of 5 participants and AVCD training for both participants. However, overselection of stimuli occurred for 20% of AVCD mastered targets, suggesting a false positive for acquisition of those targets. Maintenance was similar across conditions and experiments.